Knowledge Management for Development and Innovation to Improve Quality and Minimise the Impact of Employee Turnover at PT Daekyo Indonesia - Suyono, Ainaya Fathia (INOVASI, 2025)
This study analyzes the implementation of Knowledge Management (KM) for development and innovation to improve quality and minimize the impact of employee turnover at PT Daekyo Indonesia. The KM maturity assessment using the APO KM assessment tool indicates that PT Daekyo is at the introduction or expansion level, with a score of 141 out of 210. The lowest-scoring categories are People (18) and KM Outcomes (gap of 12), followed by Process (20). Meanwhile, the highest-scoring category is Technology (23). The main factors hindering KM implementation include a lack of support and awareness regarding KM execution, an unstructured evaluation process, an unclear competency matrix, and the absence of career development pathways. To address these challenges, semi-structured interviews were conducted with senior managers, the HR team, the recruitment team, and the training team to analyze KM strengths and opportunities for improvement. The analysis resulted in eight business solutions, which were then translated into 13 implementation plans scheduled to take place from June 2025 to May 2026. This study emphasizes the importance of a structured KM implementation to enhance organizational efficiency and reduce the negative impact of employee turnover.